Incident Reporting Development: PaSIR (Patient Safety Incident Reporting) System for Better Patient Safety - Savitri Citra Budi; Sunartini Sunartini; Fatwa Sari Tetra Dewi; Lutfan Lazuardi; Nur Rokhman (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Patient safety is a global issue in the health sector, including the issue of COVID-19 transmission in hospitals. Patient safety indicators can be analyzed through incident reports. Incident reports as a primary data source, are important as a basis for quality improvement and patient safety. The electronic-based reporting system is seen as more effective in providing convenience in reporting incidents. This study aims to develop an electronic-based incident reporting system by involving users. The electronic-based incident reporting system is named PaSIR (Patient Safety Incident Reporting). The PaSIR system has functions for reporting, analysis, feedback, and presentation of incident report profiles. In addition, the PaSIR system provides facilities for monitoring incident reports in real time. Abstrak: Keselamatan pasien menjadi isu global di bidang kesehatan, termasuk isu penularan COVID-19 di rumah sakit. Indikator keselamatan pasien dapat dianalisis melalui laporan insiden. Laporan insiden sebagai sumber data primer, penting sebagai dasar peningkatan mutu dan keselamatan pasien. Sistem pelaporan berbasis elektronik dipandang lebih efektif untuk memberikan kemudahan dalam pelaporan insiden. Penelitian ini bertujuan untuk mengembangkan sistem pelaporan insiden berbasis elektronik dengan melibatkan pengguna. Sistem pelaporan insiden berbasis elektronik ini diberi nama PaSIR (Patient Safety Incident Reporting). Sistem PaSIR memiliki fungsi untuk pelaporan, analisis, umpan balik, dan penyajian profil laporan insiden. Selain itu, sistem PaSIR menyediakan fasilitas untuk memantau laporan insiden terkini.